First‐Dose Vancomycin Pharmacokinetics Versus Empiric Dosing on Area‐Under‐the‐Curve Target Attainment in Critically Ill Patients. Issue 12 (11th December 2020) - Flannery, Alexander H.; Delozier, Natalie L.; Effoe, Samuel A.; Wallace, Katie L.; Cook, Aaron M.; Burgess, David S.
Abstract : B ackground: Early attainment of target area under the curve (AUC) to minimum inhibitory concentration (MIC) ratios have been associated with clinical success, as well as lower incidence of acute kidney injury (AKI), in patients receiving vancomycin for methicillin‐resistant Staphylococcus aureus (MRSA). Critically ill patients are particularly vulnerable to poor outcomes from infection and face multiple risk factors for AKI, thus early precision dosing of vancomycin is vital in this population. We hypothesized that a personalized dosing approach, using vancomycin levels obtained after the first dose to guide further dosing, would be superior to empiric dosing in terms of AUC target attainment assessed at steady state (SS). M ethods: A retrospective cohort study of 66 critically ill adult patients admitted to the medical intensive care unit without AKI and receiving vancomycin with at least two SS concentrations obtained for AUC calculation was performed. Patients were separated into cohorts based on whether they had two concentrations assessed after the first dose of vancomycin and were subsequently dosed based on personalized pharmacokinetic calculations (first‐dose kinetics) or whether they were empirically dosed using population estimates. The primary outcome was AUC target attainment (400–600 mg hour/L) at SS. R esults: Compared with patients receiving empiric dosing by population estimates, using first‐dose kinetics to guide subsequent dosing resulted in significantly greater AUC target attainment at SS (58.6% first‐dose vs 32.4% empiric; p=0.033). Patients dosed empirically yielded more variable AUC values across a wide range compared with the first‐dose kinetics group (coefficient of variation 40.7% empiric vs 26.1% first‐dose). There was no difference in AKI up to 48 hours after SS concentrations between the two dosing schemes. C onclusions: A dosing strategy using two vancomycin serum concentrations after the first dose and calculating personalized pharmacokinetic parameters to guide subsequent dosing is associated with greater AUC target attainment at SS compared with empiric dosing of vancomycin in critically ill adults with relatively stable renal function.